Effects of egg manipulations on clutch size of Australian Wood Ducks Chenonetta jubata - Briggs, S V (Wildfowl, 1991)
Egg manipulation experiments can be used to test the hypothesis that clutch size in indeterminately laying birds is limited by the level of nutrients stored by females prior to egg production. The number of eggs laid by Australian Wood Ducks was not affected by experimental removal or addition of eggs during laying. This is consistent with the hypothesis that the level of a female’s nutrient store proximately controls clutch size in this species.